Biophysical characterization of recombinant human ameloblastin - Wald, Tomáš; Bednárová, Lucie; Osička, Radim; Pachl, Petr; Sulc, Miroslav; Lyngstadaas, Stale Petter; Slaby, Ivan; Vondrášek, Jiří (European journal of oral sciences, 2011)
Ameloblastin (AMBN) is a protein expressed mainly during dental hard tissue development. Biochemically, it is classified as an intrinsically disordered protein (IDP). Its biological role remains largely unknown; however, the question of AMBN function will undoubtedly be connected to its structural properties and its potential for protein-protein and protein-cell interactions. A basic biophysical characterization of human recombinant ameloblastin (hrAMBN) and its N- and C-terminal domains by means of circular dichroism spectroscopy and dynamic light scattering showed that under physiological conditions ameloblastin is an IDP with a prevalent polyproline-II (PPII) conformation. Both the N- and C-terminal polypeptides, when expressed independently, showed different structural preferences upon heating as well as different behaviour in the presence of trifluoroethanol and CaCl(2) salt. The N-terminal peptide showed a more ordered structure with a strong tendency to adopt a helical conformation upon the addition of trifluorethanol, whereas the C-terminal domain seemed to be primarily responsible for the structural disorder of the entire AMBN molecule.
Keywords: Dental Enamel Proteins; Temperature; Recombinant Proteins; Scattering, Radiation; interakční proteinové domény a motivy; Protein Structure, Tertiary; spektrální analýza; Sodium Chloride; Trifluoroethanol; terciární struktura proteinů; Spectrum Analysis; sekvenční analýza proteinů; reagencia zkříženě vázaná; chlorid vápenatý; sekundární struktura proteinů; Protein Structure, Secondary; chlorid sodný; Circular Dichroism; osmolární koncentrace; Calcium Chloride; rekombinantní proteiny; Protein Interaction Domains and Motifs; lidé; biofyzikální jevy; Biophysical Phenomena; konformace proteinů; Humans; Sequence Analysis, Protein; cirkulární dichroismus; Osmolar Concentration; radiační rozptyl; trifluorethanol; Cross-Linking Reagents; Protein Conformation; proteiny zubní skloviny; teplota